SELF-EMPOWERMENT THROUGH ENTREPRENEURSHIP IN STUDENT BUSINESS OWNER SELLING HEALTHY FOOD - Nur Aslamiah Supli; Nurhayati Damiri; Supli Effendi Rahim (Awang Long Law Review, 2022)
This study aims to discuss how the process of self-empowerment experienced by individuals through entrepreneurship. This study uses qualitative methods and descriptive approaches using observation, literature studies, and interviews as instruments. In the process, the author found one of the motivations for the subject to become empowered is he realizes her state of unempowered, afterwards he proceeds to find her potential and also her interests, and then tries to change her state. One of the causes of the subject being unempowered is the economic factor. Results of this study showed that the subject in the study did self-empowerment efforts from the condition of being helpless and independent, the cause of the condition of the subject's powerlessness is economic factors. For this reason, in an effort to overcome this problem, the process of self-empowerment by the subject begins with the awareness stage himself that he could not remain silent and had to help their parents, then the subject takes advantage of the interests and knowledge he has and see the market potential that exists until decided to start a business selling healthy food, besides that the subject was developing business by opening branches and resellers as well as maintaining business by improving product quality starting from product ingredients to the product packaging.